2017
DOI: 10.1089/tmj.2016.0078
|View full text |Cite
|
Sign up to set email alerts
|

The Veteran-Initiated Electronic Care Coordination: A Multisite Initiative to Promote and Evaluate Consumer-Mediated Health Information Exchange

Abstract: This pilot demonstrates feasibility and value of patient access to a CCD to facilitate information sharing between VA and non-VA providers. Outreach and targeted education are needed to promote consumer-mediated health information exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“… 34 , 37 While all articles examined the care coordination of rural Veterans, study participants varied: 7 included Veterans, 33 , 39 , 40 , 42 45 5 included VA providers, 34 , 36 , 40 , 46 , 47 and 8 included Community Care or other non-VA providers. 31 , 35 , 36 , 38 , 41 , 44 , 45 , 47 Study settings included: 6 National studies, 33 , 37 , 39 , 42 , 44 , 47 6 in Northern Plains states, 31 , 35 , 36 , 38 , 41 , 43 2 in Western states 34 , 46 and 2 in New England states. 40 , 45 The Veteran health care focus of VA Community programs varied greatly: 3 on American Indian Community Care, 34 , 35 , 46 3 on sharing electronic health record (EHR) data, 31 , 44 , 47 2 on obstetrics and maternity, 39 , 42 1 on housing for the homeless, 36 1 on treatment for opioid use, 40 1 on retail immunization, 33 and 5 on interorganizational care coordination itself.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 34 , 37 While all articles examined the care coordination of rural Veterans, study participants varied: 7 included Veterans, 33 , 39 , 40 , 42 45 5 included VA providers, 34 , 36 , 40 , 46 , 47 and 8 included Community Care or other non-VA providers. 31 , 35 , 36 , 38 , 41 , 44 , 45 , 47 Study settings included: 6 National studies, 33 , 37 , 39 , 42 , 44 , 47 6 in Northern Plains states, 31 , 35 , 36 , 38 , 41 , 43 2 in Western states 34 , 46 and 2 in New England states. 40 , 45 The Veteran health care focus of VA Community programs varied greatly: 3 on American Indian Community Care, 34 , 35 , 46 3 on sharing electronic health record (EHR) data, 31 , 44 , 47 2 on obstetrics and maternity, 39 , 42 1 on housing for the homeless, 36 1 on treatment for opioid use, 40 1 on retail immunization, 33 and 5 on interorganizational care coordination itself.…”
Section: Resultsmentioning
confidence: 99%
“…Two policy and administrative strategies deemed successful by article authors were: alignment and understanding between partners and clear contractual agreement. VA and community partners leveraged their similarity or complementarity for alignment on one or more of the following: purpose, 31 , 33 – 35 , 38 – 40 , 46 scale, 33 geography, 44 or shared history or experience. 35 , 36 For example, strong alignment of purpose and complementarity of resources was demonstrated by the VA Maternity Care Coordination Program which guarantees women Veterans maternal and perinatal care through community specialists and mental health services through VA. 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final set of papers from this year's selection illustrates a variety of approaches, settings, and technologies for health information exchange. One of the studies, by Klein et al, discussed in more detail in the best paper summaries, was done across nine hospitals within the US department of Veterans’ Affairs (VA) 26 . Within the VA system, patients’ information is accessible to all clinicians who need it, but there is an increasing need for exchange of data with private physicians outside the VA.…”
Section: Resultsmentioning
confidence: 99%
“…The number of Veterans who use MHV continues to increase, with >2.9 million having identity-authenticated, premium accounts as of February 2019. 22 The effect of the MHV portal on care coordination issues has received scant attention, with the exception of some preliminary studies, suggesting that engaging patients in portal use to access laboratory information may empower them to improve information sharing between disparate providers and health care systems. 21,23 Specific to the context of diabetes, although some studies have found improved glycemic control in patient portal users, [24][25][26] there is limited evidence that use of portal features actually impacts duplicative tests.…”
Section: Va Patient Portalmentioning
confidence: 99%